Triangle Inside The Ellipse

Geometry Level 5

Point P ( 0 , 1 ) P(0,1) is on the ellipse E : x 2 + 9 y 2 = 9 E: x^2+9y^2=9 and point A ( 2 , 0 ) A(2,0) lies inside E E . A line passing through A A meets E E at points B B and C C .

If B P C = 9 0 \angle{BPC}=90^\circ , then the area of triangle B P C BPC can be written in the form m n p \dfrac{m\sqrt{n}}{p} , where m , n m,n and p p are positive integers with n n square-free and m , p m,p coprime. Find m + n + p m+n+p .


The answer is 147.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Relevant wiki: 2D Coordinate Geometry - Problem Solving

For any given slope t R t\in\mathbb{R} , the equation of the line passing through A A is given by : y = t ( x 2 ) \ell : y=t(x-2) . Let B ( x 1 , y 1 ) B(x_1,y_1) and C ( x 2 , y 2 ) C(x_2,y_2) be the intersection points of the line \ell and ellipse E E . Then the coordinates of B B and C C satisfy the system of equations { x 2 + 9 y 2 = 9 y = t ( x 2 ) . \begin{cases} x^2+9y^2=9\\ y = t(x-2). \end{cases} Thus x 1 x_1 and x 2 x_2 are the roots of the equation ( 1 + 9 t 2 ) x 2 36 t 2 x + 36 t 2 9 = 0 (1+9t^2)x^2-36t^2x+36t^2-9=0 with x 1 + x 2 = 36 t 2 1 + 9 t 2 and x 1 x 2 = 36 t 2 9 1 + 9 t 2 . ( ) x_1+x_2 = \dfrac{36t^2}{1+9t^2}\text{ and }x_1x_2 = \dfrac{36t^2-9}{1+9t^2}.\qquad(\star) Now, P B = x 1 , y 1 1 = x 1 , t x 1 ( 2 t + 1 ) \overrightarrow{PB}=\langle x_1, y_1-1\rangle=\langle x_1, tx_1-(2t+1)\rangle and P C = x 2 , y 2 1 = x 2 , t x 2 ( 2 t + 1 ) \overrightarrow{PC}=\langle x_2, y_2-1\rangle=\langle x_2, tx_2-(2t+1)\rangle . Since B P C = 9 0 \angle{BPC}=90^\circ , we have the dot product P B P C = 0 \overrightarrow{PB}\bullet\overrightarrow{PC}=0 . Using the equations of (\star), this dot product can be simplified to 0 = P B P C = x 1 x 2 + ( t x 1 ( 2 t + 1 ) ) ( t x 2 ( 2 t + 1 ) ) = ( 1 + t 2 ) x 1 x 2 t ( 2 t + 1 ) ( x 1 + x 2 ) + ( 2 t + 1 ) 2 = ( 1 + t 2 ) 36 t 2 9 1 + 9 t 2 t ( 2 t + 1 ) 36 t 2 1 + 9 t 2 + ( 2 t + 1 ) 2 = 4 ( 5 t 2 ) ( 2 t + 1 ) 1 + 9 t 2 , \begin{aligned} 0 = \overrightarrow{PB}\bullet\overrightarrow{PC} &= x_1x_2+(tx_1-(2t+1))(tx_2-(2t+1))\\ &=(1+t^2)x_1x_2-t(2t+1)(x_1+x_2)+(2t+1)^2\\ &= (1+t^2)\cdot\dfrac{36t^2-9}{1+9t^2}-t(2t+1)\cdot\dfrac{36t^2}{1+9t^2}+(2t+1)^2\\ &= \dfrac{4(5t-2)(2t+1)}{1+9t^2}, \end{aligned} which gives t = 2 5 t=\frac{2}{5} or t = 1 2 t=-\frac{1}{2} . If t = 1 2 t=-\frac{1}{2} , then P P will lie on the line y = ( x 2 ) / 2 y=-(x-2)/2 , which means one of the points B B and C C will coincide P P , a contradiction. Hence, we obtain t = 2 5 t=\frac{2}{5} . It follows that (using \star ) B C 2 = ( x 1 x 2 ) 2 + ( t ( x 1 2 ) t ( x 2 2 ) ) 2 = ( 1 + t 2 ) ( x 1 x 2 ) 2 = ( 1 + t 2 ) ( ( x 1 + x 2 ) 2 4 x 1 x 2 ) = ( 1 + t 2 ) [ ( 36 t 2 1 + 9 t 2 ) 2 4 36 t 2 9 1 + 9 t 2 ] = 36 ( 1 + t 2 ) ( 1 + 5 t 2 ) ( 1 + 9 t 2 ) 2 B C = 6 ( 1 + t 2 ) ( 1 + 5 t 2 ) 1 + 9 t 2 = 18 145 61 \begin{aligned} BC^2 &= (x_1-x_2)^2+(t(x_1-2)-t(x_2-2))^2\\ &= (1+t^2)(x_1-x_2)^2 = (1+t^2)((x_1+x_2)^2-4x_1x_2)\\ &= (1+t^2)\left[\left(\dfrac{36t^2}{1+9t^2}\right)^2-4\cdot\dfrac{36t^2-9}{1+9t^2}\right]\\ &= \dfrac{36(1+t^2)(1+5t^2)}{(1+9t^2)^2}\\ BC &= \dfrac{6\sqrt{(1+t^2)(1+5t^2)}}{1+9t^2}=\dfrac{18\sqrt{145}}{61} \end{aligned} and the distance d P d_P from P P to line B C BC is given by d P = t ( 0 ) 1 2 t 1 + t 2 = 9 29 . d_P=\dfrac{|t(0)-1-2t|}{\sqrt{1+t^2}}=\dfrac{9}{\sqrt{29}}. Therefore, [ B P C ] = d P B C 2 = 1 2 9 29 18 145 61 = 81 5 61 [BPC]=\dfrac{d_P\cdot BC}{2} = \dfrac{1}{2}\cdot\dfrac{9}{\sqrt{29}}\cdot\dfrac{18\sqrt{145}}{61}=\dfrac{81\sqrt{5}}{61} and m + n + p = 81 + 5 + 61 = 147 m+n+p=81+5+61=\boxed{147} .

Mark Hennings
Nov 22, 2015

Relevant wiki: 2D Coordinate Geometry - Problem Solving

The line with gradient m m passing through the point ( 2 , 0 ) (2,0) has equation y = m ( x 2 ) y \,=\, m(x-2) . Since the line cannot pass through P P , we must have m 1 2 m \neq -\tfrac12 . This line meets the ellipse x 2 + 9 y 2 = 9 x^2 + 9y^2 = 9 at the points ( x ± , y ± ) (x_\pm,y_\pm) , where x ± = 18 m 2 ± 3 5 m 2 + 1 9 m 2 + 1 y ± = 2 m ± 3 m 5 m 2 + 1 9 m 2 + 1 . x_\pm \; =\; \frac{18m^2 \pm 3\sqrt{5m^2+1}}{9m^2+1} \qquad y_\pm \; = \; \frac{-2m \pm 3m\sqrt{5m^2+1}}{9m^2+1} \;. The gradients of the lines joining these two points to ( 0 , 1 ) (0,1) are m ± = y ± 1 x ± = ( 9 m 2 + 2 m + 1 ) ± 3 m 5 m 2 + 1 18 m 2 ± 3 5 m 2 + 1 . m_\pm \; = \; \frac{y_\pm - 1}{x_\pm} \; = \; \frac{-(9m^2 + 2m + 1) \pm 3m\sqrt{5m^2 + 1}}{18m^2 \pm 3\sqrt{5m^2+1}} \;. These lines must be perpendicular, so that m + m = 1 m_+ m_- = -1 , and hence ( 9 m 2 + 2 m + 1 ) 2 9 m 2 ( 5 m 2 + 1 ) 324 m 4 9 ( 5 m 2 + 1 ) = 1 ; \frac{(9m^2 + 2m + 1)^2 - 9m^2(5m^2 + 1)}{324m^4 - 9(5m^2 + 1)} \; = \; -1 \;; This equation simplifies to 360 m 4 + 36 m 3 32 m 2 + 4 m 8 = 4 ( 9 m 2 + 1 ) ( 2 m + 1 ) ( 5 m 2 ) = 0 , 360m^4 + 36m^3 - 32m^2 + 4m - 8 \; =\; 4(9m^2 + 1)(2m+1)(5m-2) \; = \; 0 \;, and hence m = 2 5 m=\tfrac25 , since m 1 2 m \neq -\tfrac12 . Thus the points B , C B,C have coordinates ( 9 61 ( 8 ± 5 5 ) , 2 61 ( 10 ± 9 5 ) ) \left( \tfrac{9}{61}\big(8 \pm 5\sqrt{5}\big)\,,\,\tfrac{2}{61}\big(-10 \pm 9\sqrt{5}\big)\right) and so the distances B P , C P BP,CP are 9 61 290 ± 44 5 . \tfrac{9}{61}\sqrt{290 \pm 44\sqrt{5}} \;. The area of the right-angled triangle B P C BPC is 1 2 × 9 61 290 + 44 5 × 9 61 290 44 5 = 81 61 5 , \tfrac12 \times \tfrac{9}{61}\sqrt{290 + 44\sqrt{5}} \times \tfrac{9}{61}\sqrt{290 - 44\sqrt{5}} \; = \; \tfrac{81}{61}\sqrt{5} \;, so the answer is 81 + 61 + 5 = 147 81 + 61 + 5 = 147 .

Shift the origin to point P.Let the equation of BC in shifted frame be lX+mY=1.Point A becomes (2,-1) in the new frame.Homogenize equation of BC with new equation of ellipse to get joint equation of BP and PC in the new frame.Since BP and PC are perpendicular coefficients of x^2 and y^2 sum to zero.From this we can get equation of BC in new frame.We have the formula for area of triangle between ax^2+2hxy+by^2=0 and lx+my+n=0 as (n^2*sqrt(h^2-ab))/(bl^2-2hlm+am^2).Using this we can find the required area of triangle.

I did the same method but the answer I got was 9.Can you write the solution with equations and proper calculation using the method you have mentioned

Akshay Sharma - 5 years, 6 months ago

i too did the same way. But in the end i had to bash the area using section formula as i did not know that formula!

Prakhar Bindal - 4 years, 6 months ago
Lu Chee Ket
Nov 21, 2015

With gradient of line B C = m,

( 1 + 9 m 2 ) x 2 36 m 2 x + 36 m 2 9 = 0 (1+9m^2) x^2 - 36 m^2 x + 36 m^2 - 9 = 0

d d = m x y 2 m m 2 + 1 \frac{|m x - y - 2 m|}{\sqrt{m^2 +1}} = 1 + 2 m m 2 + 1 \frac{|1 + 2 m|}{\sqrt{m^2 + 1}}

D = ( x 1 x 2 ) 2 + ( y 1 y 2 ) 2 D = \sqrt{(x_1 - x_2)^2 + (y_1 - y_2)^2}

m 1 m 2 = 1 m_1 m_2 = -1

Excel simulation can handle these figures numerically by ease:

 1
 2
 3
 4
 5
 6
 7
 8
 9
10
11
12
13
14
15
m = 0.4 
a = 2.44    
b = -5.76   
c = -3.24   
C:  2.82988621290968,   0.331954485163872
B:  -0.469230475204763, -0.987692190081905
d = 1.67125804359347    
B C =   3.55325741669281    
Area1 = 2.969205019303; TRUE
A B =   2.90766930511517;   2.969205019303
A C =   2.04232648745823;   147
Area2 = 2.969205019303; 2.23606797749979
m_AC =  -0.23606797749979;  1.32786885245902
m_AB =  4.23606797749979;   1  20/61 
mp =    -1; 1.32786885245902

Area = 81 5 61 \frac{81 \sqrt5}{61}

81 + 5 + 61 = 147

Answer: 147 \boxed{147}

Is their any other method without Excel simulation .How would you solve it after equation(iii)

Akshay Sharma - 5 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...